Systemic therapy in the management of localized and locally advanced renal cell carcinoma: Current state and future perspectives - Berquist, Sean W; Yim, Kendrick; Ryan, Stephen T; Patel, Sunil H; Eldefrawy, Ahmed; Cotta, Brittney H; Bradshaw, Aaron W; Meagher, Margaret F; Bindayi, Ahmet; McKay, Rana R; Autorino, Riccardo; Staehler, Michael; et al. (International journal of urology, 2019)
Systemic therapy strategies in the setting of localized and locally advanced renal cell carcinoma have continued to evolve in two directions: (i) as adjuvant therapy (to reduce the risk of recurrence or progression in high‐risk localized groups); or (ii) as neoadjuvant therapy as a strategy to render primary renal tumors amenable to planned surgical resection in settings where radical resection or nephron‐sparing surgery was not thought to be safe or feasible. In the realm of adjuvant therapy, the results of adjuvant therapy phase III randomized clinical trials have been mixed and contradictory; nevertheless, the findings of the landmark Sunitinib Treatment of Renal Adjuvant Cancer study have led to approval of sunitinib as an adjuvant agent in the USA. In the realm of neoadjuvant therapy, presurgical tumor reduction has been shown in a number of phase II studies utilizing targeted molecular agents and in a recently published small randomized double‐blind placebo‐controlled study, and an expanding body of literature suggests benefit in select patients. Thus, large randomized clinical trial data are not present to support this approach, and guidelines for use of presurgical therapy have not been promulgated. The advent of immunomodulation through checkpoint inhibition represents an exciting horizon for adjuvant and neoadjuvant strategies. The present article reviews the current status and future prospects of adjuvant and neoadjuvant therapy in localized and locally advanced renal cell carcinoma.